Factors that affect quality of work life of the millennials linked to the commercial sector in Colombia (2021)
The present investigation has two aims: (1) to empirically examine the factors that affect QWL among the millennials working in the commercial sector in Colombia and (2) to investigate the role of a set of individual differences as moderators (for example, gender, educational level and type of contract) in a complete QWL model, based on the methodology of (Tarhini, Hone, & Liu, 2014). The instrument used was the Work Quality of Life Tool (Wage and Subjective Conditions) which has been validated in the previous studies. The total of 1,163 surveys were conducted with workers from the commercial sector in Colombia who belong to the generation Y or the millennial generation, that is, born between 1981 and 2000. The results show that training, promotion, wages and the relationship of the individual with their work directly and positively affect the quality of work life in the study sample. We conduct a confirmatory factor analysis based on structural equations, revealing that the majority of the hypothesis associated with gender, educational level and type of contract were supported. This study serves to support the establishment of programs, projects and management plans to generate adequate use of the talents and skills of the millennials and thus create challenging and satisfactory jobs that increase organizational productivity.